INTERNATIONAL EMPOWERMENT OF STUDENTS IN MALAYSIA ABOUT AGRIBUSINESS EDUCATION - Erlin Widya Fatmawati; Ertika Fitri Lisananti; Akbar Ali Arbai (International Journal of Engagement and Empowerment (IJE2), 2026)
International Empowerment of Students in Malaysia have goal to introduce agribusiness and marketing education concepts to elementary-level students in Malaysia through interactive and experiential learning activities. The program focuses on enhancing students’ understanding of agricultural products, marketing processes, and entrepreneurship spirit at an early age. The activity was conducted collaboratively between the service team and local partner schools through a series of simulations in which students acted as sellers and buyers of fruits and vegetables. To make the activity more realistic and engaging, the team provided play money as a medium of transaction, enabling students to experience the process of buying, selling, and negotiating prices in a fun learning environment. In addition, the program included the development of simple and contextual learning materials, such as a student activity book and digital worksheets, aligned with the students’ level of understanding. The mentoring sessions also involved local teachers to ensure sustainability and replication of the agribusiness learning model beyond the program period. The results of the activity showed increased student engagement and comprehension of basic marketing principles, as well as enhanced teacher capacity in integrating agribusiness content into classroom learning. This empowerment initiative not only fostered students’ entrepreneurial awareness but also supported the goal of global education collaboration through agribusiness knowledge sharing. The program contributed to building a foundation for sustainable education practices that align with the spirit of international cooperation and the achievement of the Sustainable Development Goals (SDGs), particularly in quality education and economic growth.